Konteks Lokal dalam Penafsiran Ayat-Ayat Toleransi dalam Kitab Tafsir Al-Mishbah Karya M. Quraish Shihab - Ahmad Deni Rustandi; Dody S. Truna; Rosihon Anwar; Asep Muhyidin (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Local Context in Interpreting Tolerance Verses in the Book of Tafsir Al-Mishbah by M. Quraish ShihabThe search for the idea of tolerance in the interpretation of the Qur'an which is popular in Indonesia is an important thing to do, given the condition of the pluralistic Indonesian nation. This study explores the local context of Indonesian textually in the interpretation of al-Mishbah by M. Quraish Shihab. This study was conducted through a textual analysis of the interpretation. The focus of this study is on the interpretation of the verses of tolerance in Tafsir Al-Mishbah, especially on five things: the interaction of believers and non-believers, coercion in religion, living together with people of different religions, the existence of people of the book [Ahl al-Kitab], and Islam as a mercy to the universe. This study finds that the local Indonesian context contained in this interpretation is in the translation and interpretation written in Indonesian. Although it is aimed at Muslims in general, it is clear that Muslims in Indonesia are part of the target. In the context of pluralism, the writing of this commentary is also intended to ground the Qur'an to a pluralistic society